A framework of project-based learning (PBL) pedagogy for graphic design education - Taneja, Kanupriya (Journal of Graphic Engineering and Design, 2025)
Design programmes commonly employ project-based learning (PBL) in studio settings, emphasising hands-on learning through real-world projects. However, there are multiple practices in the name of PBL. There is confusion about what is and what is not PBL. Furthermore, real-world or authentic projects are integral to PBL but have no clear interpretations. Many studies inform about the advantages of real-world or authentic projects; however, very few about its integration into teaching and even fewer in graphic design education. This action research proposes a framework for the clarity and application of PBL in a graphic design studio class using a real-world design project. The proposed framework in the study derived from the work by Blumenfeld et al., 1991; Krajcik & Blumenfeld, 2005, shows the implementation of a real-world project for graphic design students—an area where the PBL research is scarce. Applied in a communication design course at an Indian university, the framework imparts structure, clarity, and alignment with curricular requirements. This approach ensures successful course completion with tangible outcomes, enriching students’ portfolios. The study serves as a model for employing a comprehensive framework based on PBL, demystifies real-world or authentic projects and demonstrates how they can be tailored for holistic learning in graphic design education. Article history: Received (May 16, 2024); Revised (March 20, 2025); Accepted (April 14, 2025)